Overcoming cultural cleavages: results from a health promotion intervention among Roma: Premagovanje kulturnih razlik: Rezultati programa promocije zdravja v romski skupnosti - Zelko, Erika; Švab, Igor (Acta Medico-Biotechnica, 2021)
Purpose: The “SASTIPE” (health in Romani language) pilot project grew from the increasing awareness that the Roma generally have not participated in community-based healthy lifestyle promotion programs. The increasing burden of chronic disease and awareness of the need for a healthier lifestyle amongst the Roma have contributed to the development of an intervention program that was implemented in Roma settlements.Method: The program took place in nine Roma settlements from December 2012 to March 2013. We provided workshops focused on diabetes, chronically pulmonary diseases (COPD), healthy foods and blood pressure, and emergency preparedness and used specific materials that were developed together with the Roma. Quantitative data was collected using the adapted and validated versions of the EUROPREV and EuroQol questionnaires before and after the intervention. The assessment of the pilot project was made with data from the responders in the intervention group and the control group (response rates 53% and 74%, respectively), where the control group were populations that did not preform any other activities.Results: The program increased knowledge about some observed medical parameters in the intervention group (p
Keywords: Health promotion; intervention; Roma